Reasons for the Decline in the Planning Standard in School Evaluation Results: from the Perspective of School Principals in the Tan’eem Education Office, Makkah - Al-Malki, Ali Atiyah Ali (Journal of Educational and Psychological Sciences, 2025)
The study aimed to identify the reasons behind the low level of the planning standard in school evaluation results from the perspective of school principals in the Tan’eem Education Office in Makkah. It explored the administrative and personal factors affecting the preparation and implementation of operational plans. To achieve this objective, the study employed a descriptive survey methodology, targeting a sample of 130 school principals. Data were collected using a questionnaire that focused on two main dimensions: administrative and personal reasons for the decline in the planning standard. The findings indicated that the planning standard received a moderate rating in both dimensions, suggesting that planning-related issues exist but are not critical barriers. Administrative factors, such as excessive administrative burdens, budget delays, and insufficient funding, were among the primary obstacles negatively impacting planning. Additionally, personal factors, including feelings of exhaustion, work-related stress, and lack of support and recognition, significantly contributed to the decline in the planning standard. Moreover, no statistically significant differences were found in participants' responses based on school level or years of service, indicating that planning challenges are common across different schools and administrative levels.
Keywords: Planning standard; education offices; school evaluation